PEMBERDAYAAN MASYARAKAT DESA MELALUI PROGRAM PENDAMPINGAN BELAJAR DAN EDUKASI KESEHATAN ( MENCUCI TANGAN DAN PEMAKAIAN MASKER ) PADA MASA PANDEMI COVID-19 DI DESA KETAON, BANYUDONO, BOYOLALI - ANTIK PUTRI UTAMI; MARGARETHA PRABA AULIA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Real work lectures (KKN) are a series of student service activities to the community in a certain area as a form of the implementation of the Tri Dharma of Higher Education. KKN which is usually carried out in groups is transformed into an implementation independently from each student’s home. Boyolali University held a KKN that was different from the previous year because of the pandemic conditions that ocured in regions in Indonesia so that is was not possible for direct drops to the regions and implementation independently. The implementation of KKN starts from February 21, 2021 to March 31, 2021 in RT 16 RW 02 Tegalan Village, Ketaon Sub-district, Banyudono sub-district, Boyolali District. The work programs carried out include learning assintace from for children, educatin on proper hand washing, wearing masks when leaving the house. The implementation of the KKN program is expected to increase the knowledge and insigh of the residents of RT 16 RW 02, Ketaon Village, Ketaon sub-district, Boyolali district regarding covid-19, so that it can increase citizen awareness and can help break the chain of the spread of covid-19.